A horizon of (im)possibilities : a chronicle of Brazil's conservative turn - Hatzikidi, Katerina; Dullo, Eduardo (Institute of Latin American Studies, 2021)
The 2018 presidential election result in Brazil surprised and shocked many. Since then, numerous debates and a growing body of texts have attempted to understand the country's so-called 'conservative turn'. A gripping in-depth account of politics and society in Brazil today, this new volume brings together a myriad of different perspectives to help us better understand the political events that shook the country in recent years. Combining ethnographic insights with political science, history, sociology, and anthropology, the interdisciplinary analyses included offer a panoramic view on social and political change in Brazil, spanning temporal and spatial dimensions. Starting with the 2018 presidential election, the contributors discuss the country's recent -or more distant- past in relation to the present. Pointing to the continuities and disruptions in the course of those years, the analyses offered are an invaluable guide to unpacking and understanding the limits of Brazilian democracy, including what has already come to pass, but also what is yet to come.